Effect of Non-Genetic Factors on Different Genetic Group of Buck’s Semen Quality and Quantity at National Livestock Breeding Center, Nepal - Bastola, R.; Kolachhapati, M.R.; Gorkhali, N.A.; Poudel, R.; Sharma, S.; Sapkota, S. (Nepalese Veterinary Journal, 2018)
This study was conducted to assess the quality and quantity aspects of different genetic group of buck’s semen used for Artificial Insemination (AI) at National Livestock Breeding Centre (NLBC), Pokhara. For this, records from different breeds and genetic groups of buck semen collected over 3 years (2014-2016) were analyzed. Parameters such as volume, density, mass motility, initial motility concentration and post thaw motility were analysed for various non-genetic factors like year, season, green based feeding. Data were analyzed by least square method using Harvey 1990 software package. The result showed that different genetic group of bucks (P<0.001) have highly significant effect (P=0.00) on volume of semen. Significant interaction (P=0.01, 0.001) was observed between year and season on volume and density of the semen. Similarly, different genetic group of bucks had significant effect on density (P=0.03). Year showed a significant effect (P=0.02) on initial motility of the buck semen. Similarly, significant interaction between year and season on initial motility percentage (P=0.01) and post thaw motility percentage (P=0.00) was found. Likewise, year has a significant effect (P=0.01) on the Post thaw motility percentage (P=0.03) of the semen. Also, a significant effect of different breed of buck was found on post thaw motility percentage (P=0.00). In addition, the average post thaw motility percentage semen of all the genetic groups of bucks was above 52% which is considered as a good percentage for the success of AI. This result might be due to use of egg yolk free extender which is soya-based protein. Moreover, adoption of new buck semen processing technologies might further improve the semen quality and long term storability along with better management and distribution of these buck semen by Government of Nepal through livestock unit at different municipalities will improve the conception rate and save huge effort and investment for the importation of buck semen.